Establishing Model, Measures and Methods for Developing Quality of Life Among the Handicapped in Thai Society - Homsombat, Poolsak (Dhammathas Academic Journal, 2020)
The objectives of this research are: 1) To study the quality of life of the handicapped in Thai society; 2) To study factors affecting the quality of life of the handicapped in Thai society; 3) To create model, measures and methods for developing quality of life among the handicapped in Thai society. Mixed research method was used by providing questionnaires among sampling group of 188 persons and interviewing target group of 28 persons. The results of this research are as the followings: 1. The quality of life of the handicapped in Thai society in total is at moderate level. The handicapped with different sex,age, level of educationand income have different quality of life in total with significant statistics at the level of 0.05. 2. Factors affecting quality of life of the handicappedin Thai society in total is at the moderate level. The handicapped with different sex, age and income have different opinion on factors affecting quality of life of the handicapped in Thai society in total with significant statistics at .05 levels. The rest has been found that the handicapped with different level of education do not have different opinion on quality of life of the handicapped in Thai society in total. 3. Creating model, measures and methods for developing quality of life of the handicapped in Thai societythat necessarily relies on the following five factors: 1) Promoting the handicapped to equally get access to their rights in public welfare and facilities2) Enhancing strength and cooperation among organizations of the handicapped and their networks 3) Integrating and driving the policies for the handicapped into a concrete practice 4) Developing potentials and creating constructive attitude towards the handicapped and their disability 5) Supporting and promoting Buddhist organizations to have their roles in rehabilitating the handicapped in physical, mental, social, environmental and spiritual aspects.